Read4Respect Service-Learning Project: Motivating and Engaging Students in Reading - Valerie Zelenka; Eric Deneault; Keith Dreiling; Beth Walizer (The Advocate, 2015)
This paper discusses an afterschool servicelearning project implemented over the course of the school year in a low SES elementary school. This project offered a sustained, coordinated effort to motivate and engage 57 struggling readers in a skillsbased literacy tutoring program. A paired two-sample ttest was conducted to determine if there was a significant increase in scores from the reading attitude pre-survey to the postsurvey for the fall 2014 and spring 2015 semesters. Increases in attitude scores were found for 13 of the 20 survey questions with three of the increases found to be significant.